The Influence of Social, Economic, and Ecological Aspects on Village Development Index in Indonesia - Herlina, Dian Nora; Windhani, Kikin (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
Sustainable Development Goals (SDGs) for villages aim to realize inclusive, sustainable development based on community needs. However, the improvement of road infrastructure has not been accompanied by an increase in the quality of village development, as evidenced by the ratio of very underdeveloped and underdeveloped villages being greater than that of advanced or independent villages. This research aims to analyze the influence of social aspects (health, education, access to sanitation, access to the internet), economic aspects (financial services and insurance, road infrastructure), and ecological aspects (air quality, disaster risk) on the Village Development Index in Indonesia for the years 2021-2023. The research method employs panel data regression analysis across 31 provinces in Indonesia. Research findings indicate that education, sanitation access, internet access, and financial services and insurance have a significantly positive impact, while road infrastructure and disaster risk have a significantly negative impact on the Village Development Index in Indonesia. This implies that both local and central governments need to promote improvements in access to education in particular, ensure the development and maintenance of adequate sanitation facilities, expand internet access, encourage enhancements in microfinance services, improve access to and quality of roads, and enhance anticipation or mitigation of natural disasters in rural areas.